Zdrowotne uwarunkowania niepełnosprawności osób starszych = Health determinants of disability in the elderly - Oliwia Beck; Mateusz Łakomski; Kornelia Kędziora-Kornatowska; Agnieszka Radzimińska; Magdalena Weber-Rajek; Walery Zukow (Kazimierz Wielki University, 2016)
Beck Oliwia, Łakomski Mateusz, Kędziora-Kornatowska Kornelia, Radzimińska Agnieszka, Weber-Rajek Magdalena, Żukow Walery. Zdrowotne uwarunkowania niepełnosprawności osób starszych = Health determinants of disability in the elderly. Journal of Education, Health and Sport. 2016;6(9):471-478. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.151618 http://ojs.ukw.edu.pl/index.php/johs/article/view/3869       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016.     Zdrowotne uwarunkowania niepełnosprawności osób starszych Health determinants of disability in the elderly   Oliwia Beck¹ ², Mateusz Łakomski², Kornelia Kędziora-Kornatowska², Agnieszka Radzimińska3, Magdalena Weber-Rajek3, Walery Żukow4   1Katedra Zdrowia Publicznego, Wydział Nauk o Zdrowiu, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy UMK w Toruniu 2Katedra i Klinika Geriatrii, Wydział Nauk o Zdrowiu, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy UMK w Toruniu 3Katedra Fizjoterapii, Zakład Podstaw Fizjoterapii, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, UMK w Toruniu 4Uniwersytet Kazimierza Wielkiego, Bydgoszcz   Streszczenie Artykuł przedstawia aktualną i prognozowaną sytuację demograficzno - społeczną Polski oraz jej konsekwencje, wyrażające się we wzroście liczby osób starszych z niepełnosprawnością. Podjęto w nim kwestie związane z definiowaniem niepełnosprawności oraz medycznymi i zdrowotnymi jej uwarunkowaniami. Problemy starszych osób niepełnosprawnych wynikające z występujących w tej grupie ograniczeń funkcjonalnych i zależności od otoczenia, a także kwestie edukacji zdrowotnej społeczeństwa stanowią zasadniczą część pracy. Tytułem podsumowania przeanalizowano wynikające z powyższych zagadnień obecne i przyszłe wyzwania stojące przed systemem opieki zdrowotnej państwa i przedstawiono rekomendacje. Słowa kluczowe: zdrowie, starzenie się, niepełnosprawność, niesamodzielność   Abstract The paper describes the current and predicted sociodemographic situation of Poland along with its consequences, expressed in the growing number of the elderly and the disabled. Issues concerning defining disability, as well as medical and health determinants of that state, are discussed. Problems of elderly and disabled people resulting from their functional restrictions and dependency on others comprise the body of the paper. The analysis of current and upcoming challenges, together with recommendations for the health care system of the state, summarizes the article. Keywords: health, ageing, disability, dependency